The Development of Problem Based Learning Desmos-Assisted Digital Worksheet for Trigonometry Function - Yulianti, Neneng; Putra, Harry Dwi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Research purposes was  to develop digital Student Worksheets (LKPD) based on the Problem Based Learning (PBL) approach on trigonometry material using Desmos and to find out the feasibility analysis this worksheets. The research method uses Analysis Design Development Implementation Evaluation (ADDIE). In the analysis stage, literature studies, observations and interviews were carried out to find out  difficulties during blended learning, followed by designing and developing media by utilizing the various features  in Desmos. At the implementation stage,  validation is carried out to test the feasibility of the e-LKPD  by two experts on media and materials. The results of the expert validation on the feasibility of the e-LKPD on the media aspect obtained a value of 73,14% with the appropriate criteria, while the material aspect obtained a value of 75,00% with the appropriate criteria. The most prominent of this e-LKPD is animation which shows the interactiveness and able to spur studentsÂ  to discover and generalize the concept of the graph of the sine function of the unit circle. In the final stage a limited test was conducted in a small group of six students at SMAN 1 Lembang and get a response score of 76,74% was obtained with very good criteria.